(untitled) (TAJ: Journal of Teachers Association, 2019)
Breast cancer is the second common cause of cancer death in women of our country. Treatment of breast cancer depends on a number of parameters known as pathological and biological prognostic markers. Knowledge of the tumour grade would avoid under treatment of high grade carcinomas and over treatment of low grade carcinomas. Out study evaluated the feasibility of a grading system on FNA of duct cell carcinoma (NOS) and its ability to predict the histologic grade of the surgical specimens. The two widely practice grading system; Robinson’s cytological grading and Scraff Bloom Richardson histological grading system were utilized for this purpose. Various reports quote varied reproducibility, ranging from 50 to 90% correlation between histologic and cytologic grade. In this study, the correlation between histologic and cytologic grade is 86.3%. In this study association between grading by FNAC and histology was statistically highly significant (χ2=27.66, df=1, p<0.05) sensitivity 100% and specificity 58.33%. Maximum correlation was noted in grade-I. Out of 53 cases 46 showed correlation between histologic and cytologic grading, only 7 cases showed no correlation. Histologic grade were higher than cytologic grade and maximum were within one grade difference. The reasons for discrepancies between cytologic and histologic grades appear to be due to lack of histologic parameter of mitosis in cytology. In this study, a total 57 cases of breast lump were selected for FNAC; of them 56 were female and 1 male. Out of 57 cases, 44 cases had duct cell carcinoma (DCC) and 13 cases had atypical finding such as small cells, inconspicuous nucleoli. Fifty three cases were diagnosed as DCC and lobular carcinoma by histopathological study. After confirmation of the diagnosis of breast cancer by histopathological examination ER, PR determination by immunohistochemistry was done in all 53 cases of breast cancer. FNAC has good sensitivity (85.29%) and very high specificity (100%). It can replace the open biopsy in the majority cases of clinically malignant disease. TAJ 2018; 31(1): 1-8